Preimplantation genetic testing for complex chromosomal rearrangements: clinical outcomes and potential risk factors - Liu, Dun; Chen, Chuangqi; Huang, Qianwen; Dong, Yunqiao; Xu, Liqing; Dong, Mei; Zhu, Zhenghong; Huang, Li; Wang, Fang; Zhang, Lijia; Zhang, Xiqian; Liu, Fenghua (Frontiers in Genetics, 2024)
Objective: Complex chromosome rearrangements (CCR) are rare structural abnormalities involving at least three breakpoints, categorized into three types based on their structure: type A (three-way rearrangements), type B (double two-way translocations), and type C (exceptional CCR). However, thus far, limited data exists on preimplantation genetic testing for chromosomal structural rearrangements (PGT-SR) in CCR carriers. This study aims to evaluate the clinical outcomes and influencing factors of PGT-SR in couples with CCR. Methods: 15 couples with unique CCR recruited from 793 couples following PGT-SR between January 2017 and May 2023. In addition, a total of 54 CCR cases, 39 previously reported as well as 15 newly added, were included in the analysis of factors associate with normal/balanced embryos. Results: A total of 100 blastocysts were biopsied and analyzed in 15 CCR couples after 17 PGT-SR cycles, with 16.0% being euploid, 78.0% aneuploid and 6.0% mosaic. 11 normal/balanced embryos and one mosaic embryo were transferred, resulting in eight live births. Furthermore, based on the combined data from 54 CCR carriers, the proportion of normal/balanced embryos was 10.8%, with a significant decrease observed among female carriers compared to male heterozygotes (6.5% vs. 15.5%, P = 0.002). Type B exhibited the lowest rate of euploid embryos at only 6.7%, followed by type A at 11.6% and type C at 14.0%, although the differences were not significant (P = 0.182). After completing the multivariate generalized estimating equation (GEE) analysis, type B (P = 0.014) and female carrier (P = 0.002) were identified as independent risk factors for fewer euploid embryos. Conclusion: The occurrence of balanced CCR in patients with reproductive abnormalities may be more frequent than we expected. Despite the proportion of normal/balanced embryos being significantly low, which can be influenced by CCR type and carrier’s sex, PGT-SR may improve the reproductive outcomes among CCR cases. These findings can optimize the clinical management and genetic counseling of CCR carriers seeking assisted reproductive technology (ART).